2013
DOI: 10.1017/s0265051713000041
|View full text |Cite
|
Sign up to set email alerts
|

The intermediate piano stage: exploring teacher perspectives and insights

Abstract: While many piano students successfully progress beyond beginner status to reach what is commonly referred to as the intermediate stage, there is minimal research specific to this area of practice. This is despite the fact that there is a high drop-out rate at this stage. This research study therefore set out to develop an in-depth understanding of the key issues of relevance from the perspective of the teachers who work with intermediate piano students. In order to develop a substantial body of data and theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It is recognized that many piano students quit lessons before even reaching a moderate mastery of the piano, and the pre-teen or early adolescent years seem to be the major point of dropout (Barry 2007;Seo 2010). Researchers Daniel and Bowden (2013) found more than half of the music teachers surveyed believe the early teenage stage of piano learning "involves a high drop-out rate" (255). Literature has demonstrated that as piano students grow older, they become fewer, such that "the percentage of boys taking lessons dropped from 33.6% when they were 9 years old, to 9.8% when they were 17" (Cremaschi et al 2015, 15).…”
Section: Introductionmentioning
confidence: 99%
“…It is recognized that many piano students quit lessons before even reaching a moderate mastery of the piano, and the pre-teen or early adolescent years seem to be the major point of dropout (Barry 2007;Seo 2010). Researchers Daniel and Bowden (2013) found more than half of the music teachers surveyed believe the early teenage stage of piano learning "involves a high drop-out rate" (255). Literature has demonstrated that as piano students grow older, they become fewer, such that "the percentage of boys taking lessons dropped from 33.6% when they were 9 years old, to 9.8% when they were 17" (Cremaschi et al 2015, 15).…”
Section: Introductionmentioning
confidence: 99%